2008
DOI: 10.1063/1.2832746
|View full text |Cite
|
Sign up to set email alerts
|

Polarizable interaction potential for water from coupled cluster calculations. I. Analysis of dimer potential energy surface

Abstract: A six-dimensional interaction potential for the water dimer has been fitted to ab initio interaction energies computed at 2510 dimer configurations. These energies were obtained by combining the supermolecular second-order energies extrapolated to the complete basis set limit from up to quadruple-zeta quality basis sets with the contribution from the coupled-cluster method including single, double, and noniterative triple excitations computed in a triple-zeta quality basis set. All basis sets were augmented by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 122 publications
7
114
0
Order By: Relevance
“…Calculations on the effects of monomer flexibility [18][19][20] have shown that this quantity a͑0͒ + a͑1͒ decreases when the H 2 O monomers are relaxed. It is striking in this respect, see Table VI, that the other pure ab initio potential that gives very good agreement with the experimental data, the 6D CC-pol potential, 10,17,21 gives practically the same deviation from experiment for a͑0͒ + a͑1͒ as the HBB0 and HBB potentials. It is most probable that all of these potentials have reached the "rigid monomer limit" of the acceptor splitting.…”
Section: Vibration-rotation Tunneling Spectrum Of the Water Dimersupporting
confidence: 66%
“…Calculations on the effects of monomer flexibility [18][19][20] have shown that this quantity a͑0͒ + a͑1͒ decreases when the H 2 O monomers are relaxed. It is striking in this respect, see Table VI, that the other pure ab initio potential that gives very good agreement with the experimental data, the 6D CC-pol potential, 10,17,21 gives practically the same deviation from experiment for a͑0͒ + a͑1͒ as the HBB0 and HBB potentials. It is most probable that all of these potentials have reached the "rigid monomer limit" of the acceptor splitting.…”
Section: Vibration-rotation Tunneling Spectrum Of the Water Dimersupporting
confidence: 66%
“…The value of D e from the HBB+ 3B potential is too small, which is due to the fact that the HBB pair potential is too shallow. 28 In Tables II and III, we see that the torsional frequencies of both ͑H 2 O͒ 3 and ͑D 2 O͒ 3 do not change much by the inclusion of the three-body induction terms: the splittings decrease for ͑H 2 O͒ 3 by 2%-3%. The frequencies are increased by 2%-3% compared to the CC-pol͑2B͒ values when the complete three-body potential is used, including exchange.…”
Section: Resultsmentioning
confidence: 84%
“…31 turned out to reproduce the spectra of ͑H 2 O͒ 2 and ͑D 2 O͒ 2 very precisely, even more so than the best of the VRT͑ASP-W͒ potentials 42 fitted to the latter spectrum. Several of these potentials [26][27][28][29]42,44 have also been used in molecular dynamics ͑MD͒ simulations of liquid water. An extensive discussion of their performance in this respect can be found in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations